2017
DOI: 10.1002/adhm.201701211
|View full text |Cite
|
Sign up to set email alerts
|

Nanocarrier‐Mediated Photochemotherapy and Photoradiotherapy

Abstract: Photothermal therapy (PTT) and photodynamic therapy (PDT) both utilize light to induce a therapeutic effect. These therapies are rapidly gaining importance due to the noninvasiveness of light and the limited adverse effect associated with these treatments. However, most preclinical studies show that complete elimination of tumors is rarely observed. Combining PDT and PTT with chemotherapy or radiotherapy can improve the therapeutic outcome and simultaneously decrease side effects of these conventional treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 157 publications
(148 reference statements)
0
26
0
1
Order By: Relevance
“…Yoon et al7 have found that PDT with ALA-hx (hexenyl ester of 5-aminolaevulinic acid) more efficiently produced reactive oxygen species (ROS) and suppressed MCF-7/ADR cells viability; the findings suggest that ALA-hx PDT may be used as a therapeutic alternative for drug-resistant breast cancer 7. In addition, the combination of PDT and chemotherapy always has potential advantages compared with traditional treatments, such as high selectivity, minimal invasiveness, and effectiveness in overcoming chemotherapy drug resistance 810…”
Section: Introductionmentioning
confidence: 99%
“…Yoon et al7 have found that PDT with ALA-hx (hexenyl ester of 5-aminolaevulinic acid) more efficiently produced reactive oxygen species (ROS) and suppressed MCF-7/ADR cells viability; the findings suggest that ALA-hx PDT may be used as a therapeutic alternative for drug-resistant breast cancer 7. In addition, the combination of PDT and chemotherapy always has potential advantages compared with traditional treatments, such as high selectivity, minimal invasiveness, and effectiveness in overcoming chemotherapy drug resistance 810…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is a tendency to explore nanomaterials with excellent biocompatibility which can be prepared by a simple synthesis. Moreover, light source plays a vital role in PDT and PTT, so it is indispensable to find the ideal wavelength of light [ 203 , 204 ].…”
Section: Chemo-photothermal Combination Therapymentioning
confidence: 99%
“…优点是PTT驱动诱导肿瘤内热疗, 同时增加肿瘤组织 内的血流量, 改善氧合作用, 从而使细胞对辐射更敏 感. 用于该组合的纳米材料呈现高NIR吸光值并且可 以产生局部的温度升高, 同时具有放射增敏作用 [96] . Li等人 [97]…”
Section: 通过Ptt升高局部肿瘤温度进行的热疗已被证 明是Rt的有力增强剂 结合这两种治疗方案的主要unclassified